1992
DOI: 10.1002/1097-4679(199201)48:1<54::aid-jclp2270480107>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

The detection of malingering and deception with A short form of the MMPI-2 based on the L, F, and K scales

Abstract: This project examined the use of a short inventory based on the validity subscales from the MMPI‐2. In Study 1, 69 subjects responded to the extracted L, F, and K items and to those items when embedded in the complete MMPI‐2. Correlations between administrations were equivalent to the original test‐retest reliabilities for these scales. In Study 2, 60 subjects responded to the short‐form with instructions to be honest, fake good, or fake bad. The correct classification rate was 77% using the standard MMPI‐2 ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…There are was no recognized protocol to manage malingering if suspected. Each case is unique and will require an approach peculiar for the specific symptomatology, educational, and cultural background of the client and the secondary gain associated 23. Malingering must be differentiated from factitious and dissociative disorders as well as pseudoseizure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are was no recognized protocol to manage malingering if suspected. Each case is unique and will require an approach peculiar for the specific symptomatology, educational, and cultural background of the client and the secondary gain associated 23. Malingering must be differentiated from factitious and dissociative disorders as well as pseudoseizure.…”
Section: Discussionmentioning
confidence: 99%
“…Malingering may occur in circumstances where the person wishes to avoid responsibilities or obtain compensation in situations where benefits might be given 1. Motives of malingering in children vary from amusement, avoidance of physical and psychological discomfort, and material gain 234. These clinical manifestations also often lead to a diagnostic dilemma as it is usually confused with factitious or dissociative disorders 5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such a context, the validity scales of the MMPI or the openness scale of the Freiburg Personality Inventory (FPI) may prove useful as screening methods. Cassisi und Workman [40] demonstrate that the abbreviated form of the MMPI exclusively containing the items of the validity scales are as efficient in identifying a defensive response style of the patient as the use of the full version of the MMPI. Building on that, it would be conceivable to integrate the items of the validity scales in an inventory that focuses specifically on problems connected with transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…These three new scales plus the three still intact from the MMPI (i.e., F, F-K, and 0-S) offer six scales to detect faking bad in an MMPI-2 profile. Cassisi and Workman (1992) found that the F scale correctly identified more fakebad profiles (95% correct) than both the L and K scales (only 10% correct). Whereas Austin (1992) reported that the F, K, F-K, and 0 -S scales outperformed the L scale, Timbrook, Graham, Keiller, and Watts (1993) have indicated that the 0-S scale is no more useful than either F and L in the recognition of fake-bad profiles.…”
Section: Mmpi-2 Dissimulation Researchmentioning
confidence: 99%